How the Subaltern Speaks in Iksaka Banu’s “Di Ujung Belati” : A Postcolonial Study - Fajar Diana Safitri; Ine Wulandari; Hairini Nur Hanifah (Universitas Brawijaya, 2022)
Iksaka Banu’s “Di Ujung Belati is a short story set in the colonial era. The social class system established by the Dutch government at that time makes the natives difficult to speak in various spheres of life. In this study, the short story was discussed using the perspective of subalternity introduced by Spivak. The method used was the literature review method. Based on the discussion, it can be seen that the Dutch put the natives in a subaltern position in terms of gender, economy, and culture. The oppression perceived by the subaltern gives rise to resistance in the form of rebellion and betrayal towards the Dutch government. That rebellion and betrayal is the way the subaltern speaks. Even though they have succeeded in overthrowing the Dutch, the natives are under the domination of another Western power, which is Britain. This shows that the natives are not completely successful in fighting Western hegemony. In relation to the current context of globalization, “Di Ujung Belati” short story can be a form of raising public awareness of the existence of neocolonialism after colonialism is abolished.